2001
DOI: 10.1093/ndt/16.7.1364
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of biopsy‐proven glomerulonephritis in Australia

Abstract: This review has provided population-based descriptive epidemiological data on clinically significant glomerulonephritis. This data provides important clues for further studies relating to the identification of risk factors for the various types of glomerulonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
156
5
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 8 publications
20
156
5
7
Order By: Relevance
“…The incidence of MPGN has been reported to decrease over time from about 7-10% in the 1970s to about 2% during 1990-2011 [3][4][5][6][16][17][18][19]. In the present study, among the 26,535 patients with biopsy-confirmed disease, 593 (2.2%) patients were registered as having a histopathology of MPGN types I and III.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…The incidence of MPGN has been reported to decrease over time from about 7-10% in the 1970s to about 2% during 1990-2011 [3][4][5][6][16][17][18][19]. In the present study, among the 26,535 patients with biopsy-confirmed disease, 593 (2.2%) patients were registered as having a histopathology of MPGN types I and III.…”
Section: Discussionmentioning
confidence: 44%
“…Further, 332 out of the 26,535 (1.3%) patients were registered as primary MPGN. In a comprehensive epidemiological study, the lesion of MPGN was observed in about 2% of patients with biopsy-confirmed glomerulonephritis in the Australia [3] and United States [19]. As for primary MPGN, a recent report from Japan has showed a 1.2% incidence of primary MPGN in a total of 6,369 renal biopsies [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 128,057,352 people resided in Japan in 2010, the estimated rate of renal biopsy was 140.6 to 164.0 per million population. This rate was higher than that in Romania [24], Spain [25], the Czech Republic [10], Denmark [26], and Scotland [27], was similar to that in France [28], and was lower than that in USA, Finland [29], and Australia [30].…”
Section: Discussion and Commentsmentioning
confidence: 62%
“…IgA nephropathy is the most common primary glomerulopathy among all races from Europe [3][4][5], Asia [6,7], and Australia [8] with the exception of the black race [9]. Nair et al demonstrated that IgA nephropathy patients increase as the primary glomerulopathy among young adults (20-39 years old) in the USA [10].…”
Section: Introductionmentioning
confidence: 99%